Evaluasi Uji Keturunan Cendana (Santalum Album Linn.) Umur 8 Bulan Di Kabupaten Timor Tengah Utara-Nusa Tenggara Timur - Sumardi Sumardi; Hery Kurniawan; Misto Misto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
Sandalwood (Santalum album L.), a native plant of Nusa Tenggara Timur, has a very high economic value due to santalol content in the heartwood. Currently the gap between demand and production capability of sandalwood oil is high. Productivity and quality of sandalwood can be increased through a series of tree improvement activities, such as establishing a progeny test to produce genetically improved seed. Balai Penelitian Kehutanan Kupang has established a first generation progeny test of sandalwood at Timor Tengah Utara regency, Nusa Tenggara Timur province to improve the productivity of heartwood, rendemen and santalol contents. The trial was laid out in Incomplete Block Design (IBD) consisting of 65 families, 3 tree-plots, 5 replications with a spacing of 4 x 4 m. This study was aimed to evaluate the growth of sandalwood progeny test at eight months after planting. The result of study showed that average growth of height and diameter are 48.60 cm and 4.55 mm, respectively. The estimates of family and individual heritability for height are 0.06 and 0.03,respectively, while for diameter are 0,16 and 0,10. Genetic correlation between the heightand diameter is 0.87.